Coagulation and metastasis: what does the experimental literature tell us?. (21st May 2013) - Gil‐Bernabé, Ana M.; Lucotti, Serena; Muschel, Ruth J.
Summary Inhibition of coagulation greatly limits cancer metastasis in many experimental models. Cancer cells trigger coagulation, through expression of tissue factor or P‐selectin ligands that have correlated with worse prognosis in human clinical studies. Cancer cells also affect coagulation through expression of thrombin and release of microparticles that augment coagulation. In the cancer‐bearing host, coagulation facilitates tumour progression through release of platelet granule contents, inhibition of Natural Killer cells and recruitment of macrophages. We are revisiting this literature in the light of recent studies in which treatment of clinical cohorts with anticoagulant drugs led to diminished metastasis.